2004
DOI: 10.1021/om049749z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the [MeAl(2-py)3]- Anion and Its Application as a Stable and Mild Pyridyl-Transfer Reagent (2-py = 2-Pyridyl)

Abstract: The thermally stable tris(pyridyl) Al(III) complex [MeAl(2-py)3Li·THF] (1·THF), obtained from the reaction of lithiopyridine [2-pyLi] with MeAlCl2 (3:1 molar equiv, respectively), functions as a pyridyl-transfer reagent, as exemplified by the reaction of 1·THF with CuCl (1:1 molar equiv), which gives the Cu(I) organometallic [{Cu(2-py)}3]∞ (2). The solid-state structures of 1, the dimer [MeAl(2-py)3Li]2 ([1]2), and 2 are reported. Complex 2, which cannot be obtained by direct reaction of [2-pyLi] with CuCl, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 18 publications
8
53
0
Order By: Relevance
“…In contrast to the behaviour of the dimeric unsubstituted complex [MeAl(2‐py) 3 Li] 2 ,6a no evidence for a monomer/dimer equilibrium is detected in solution for desolvated 1 . Room‐temperature 1 H and 7 Li NMR spectroscopic studies in [D 8 ]toluene show the presence of a single compound in solution, with no variation in the spectra observed on changing the concentration.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In contrast to the behaviour of the dimeric unsubstituted complex [MeAl(2‐py) 3 Li] 2 ,6a no evidence for a monomer/dimer equilibrium is detected in solution for desolvated 1 . Room‐temperature 1 H and 7 Li NMR spectroscopic studies in [D 8 ]toluene show the presence of a single compound in solution, with no variation in the spectra observed on changing the concentration.…”
Section: Resultsmentioning
confidence: 69%
“…The extreme steric congestion of the aluminate ion is witnessed in the solid‐state structure of 1 ⋅THF, which has a highly distorted Li–THF coordination environment. In light of this apparently weak coordination of THF to Li + , we decided in our preliminary studies to explore the desolvation of 1 ⋅THF, anticipating the formation of a dimeric complex [ 1 ] 2 , which would be analogous to the dimeric complex [MeAl(2‐py) 3 Li] 2 formed by desolvation of THF using the unsubstituted complex [MeAl(2‐py) 3 Li⋅THF] (Scheme ) 6a…”
Section: Resultsmentioning
confidence: 99%
“…The calculated structural parameters are in good agreement with the available X-ray data. 3,19,25,27,28 For instance, for 1c, the calculated Au + -N and Au + -Au + bond distances and the N-Au + -N bond angle values are 2.002 Å, 3.360 Å, and 179.7°, the correspondent experimental values are 2.003 Å, 3.387 Å, and 177.0°, respectively. Excellent agreement between calculated and experimental structural parameters is also observed in 3a, 3c, 7c, and 8c (Fig.…”
Section: Geometriesmentioning
confidence: 89%
“…26 It has also been shown that CTCs containing the same ligands but with different metal ions such as Cu + , Ag + , or Au + differ not only in their structural parameters, but also in their electronic structure. 28 Fackler and coworkers have synthesized and determined the crystallographic structures of complexes like [Au 3 (μ-3,5-Ph 2 pz) 3 ], [Ag 3 (μ-3,5-Ph 2 pz) 3 ], and [Cu 3 (μ-3,5-Ph 2 pz) 3 ], 29,30 showing that the gold complex exhibits a planar structure, while silver and copper complexes show significant deviation from planarity as well as different metal-ligand bond lengths, Au-N bonds are slightly shorter than Ag-N and Cu-N. Another important feature of CTCs is the amplified π-acidity and π-basicity that they present. [1][2][3]6,[12][13][14][15] The π-acid/ base properties are responsible for the formation of the supramolecular extended stacks with arenes.…”
Section: Introductionmentioning
confidence: 99%
“…[5b] We have been particularly interested in aluminates 3 ] À ;F igure 1 B)a s they are unusual in this area in having an overall negative charge( rather than being neutral). [3a] As one of the few anionic members of the tris(pyridyl) family,t hey exhibit as tronga ffinity for metal cations and have extensive coordination chemistry with ab road range of transition metals, [6] main-group metals, [7] and lanthanides. [8] The closely related tris (2-pyridyl)borates [3b, 9] have also attracted recent interest, stemmingf rom their potential applications in polymer and supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%